PREDICTION AND DAMAGE ANALYSIS OF THE POSTBUCKLING FOR MULTI-SPAR COMPOSITE BOX - YUAN Fei; CHAI YaNan; ZHANG AYing (Jixie qiangdu)
as multi-spar composite box has been used for many airplanes,in order to assure structure security,it is necessary to study the mechanical properties of multi-spar composite box. Aiming at the buckling and postbuckling problems,buckling behavior and damage process of multi-spar composite box under bending-shearing load is researched in this paper. A self-defined nonlinear degradation rule was presented to simulate the propagation of the interface elements which were discretized with solid elements. In this model,the onset and propagation of damage can be predicted by quadratic failure criteria and mixed-mode strain energy release rate criteria respectively. cohesive elements are used to simulate the adhesive layer between skin and flange.composite structures were discretized with continuum shell elements. In this paper,a failure algorithm based upon Puck’s failure theory has been developed. Based on ABAQUS,a material degradation rule of composite was presented. The process of damage initiation,propagation and failure of the stiffened composite panels was simulated in detail. At last,a good agreement between tests and numerical prediction was observed.